Habilidades sociales y tipos de comportamientos en los estudiantes de la Institución Educativa N°64479 Pastor Valencia Peña Bilingüe Intercultural, Cushillo Cocha 2025 - Parente Serra, Llesy Geomali (2025)
The present study aimed to determine the relationship between social skills and behavior types in students of regular basic education at a bilingual intercultural educational institution. The research was of a basic type, developed under the hypothetical-deductive method with a quantitative approach, correlational scope, non-experimental variables, and a cross-sectional design. The sample was probabilistic and stratified, consisting of 170 students, to whom two standardized questionnaires were applied via survey. The results demonstrated a very strong positive correlation between social skills and behavior types (Spearman's Rho = ,922; p < .001). Furthermore, each dimension of social skills showed significant correlations: basic skills (,916), making friends (,871), conversational skills (,945), feelings and opinions (,906), problem-solving (,873), and relationship with adults (,753). It is concluded that the comprehensive development of social skills directly influences the manifestation of adaptive behaviors in the school context, thus confirming the stated objectives.